Spatial Order of Peripheral Areas in Aspects of Partition - Zygmunt, Justyna; Mach, Łukasz (Regional Barometer. Analyses & Prognoses, 2012)
The article includes the issues connected with community investment expenditures and their significant importance in local development creation. The theoretical assumptions concentrate on the investment-expenditures’ essence, and, also related, the problem of expenditures in question usage as a measure of local development. The main purpose of the empirical analysis was to present the diversity of investment expenditures, both in the static and dynamic dimension way, as well on the multidimensional comparative analysis level. The static analysis results were the basis to diagnose the expenditures shaping in the respective communities in the Kędzierzyn-Koźle district. It also created the grounds for a dynamic analysis realization. The main goal of this part of the research was to identify the dynamics of changes in investment expenditures as the base which enables expenditures in question approximation for future periods. The empirical research completion was made by forming the multidimensional-communities’ rating concerning investment expenditures.